Novel ultra-short peptide hydrogel as a potential drug nanocarrier - Silva, Joana F. G. (2019)
Considering structural aspects required to favour hydrogelation and empirical knowledge on the self-assembly of dipeptides, a new hydrogelator comprising a methionine residue and a dehydrophenylalanine residue was designed and synthesised through a low-cost synthesis route.